Monitoring of mechanized harvest operation of soybean seeds - Cassia, Marcelo T. [UNESP]; Voltarelli, Murilo A. [UNESP]; Silva, Rouverson P. da [UNESP]; Zerbato, Cristiano [UNESP]; Lima, Pedro H. de [UNESP] (Univ Federal Campina Grande, 2015)
The mechanized operation of harvesting seeds demands that the adjustments of harvesters should be dynamic, which directly affects the quality of the operation and the harvested grain. Thus, the objective of this study was to monitor, at regular intervals of time, the quality operation of harvesting of soybean seeds held simultaneously by two combine harvesters, with use of statistical control quality (SCQ). The study was conducted in a field of seed production in the region of Catalan, GO, Brazil, where the operational performance of harvesters, quantitative crop losses and qualitative losses of seeds were monitored. It was observed that the monitored harvesters were operated under similar conditions, but the adjustments in the cylinder and in the rotor rotation optimized the indexes of losses, maintaining the quality of harvested seeds. Thus, all evaluated indexes of losses both quantitative losses as the values of qualitative losses were within the limits of statistical control, which allows assigning quality and reliability for operation of mechanized harvesting of seeds.
Keywords: Glycine max; harvester grain; harvesting losses; statistical control quality (SCQ)